ADMINISTRATIVE DOCTRINE OF INCREASING THE PUBLIC SECURITY LEVEL IN COUNTRIES OF THE EUROPEAN COMMUNITY - Bezzubov, Dmytro; Khomyachenko, Svitlana (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
Тhe paper is dedicated to the problems of public security maintenance in the present-day context. Methods, techniques and strategies of public security maintenance as a scientific and public phenomenon are revealed. The levels of public security maintenance within the European Community are defined.